2014
DOI: 10.2527/jas.2013-7084
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated nitrate and cashew nut shell liquid on blood and rumen constituents, methane emission, and growth performance of lambs1,2

Abstract: Nitrate can be a source of NPN for microbial growth at the same time that it reduces ruminal methane production. The objective of this study was to evaluate the effects of 2 encapsulated nitrate products used as urea replacers on blood and rumen constituents, methane emission, and growth performance of lambs. Eighteen Santa Inês male lambs (27 ± 4.9 kg) were individually allotted to indoor pens and assigned to a randomized complete block design with 6 blocks and 3 dietary treatments: control (CTL) = 1.5% urea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 37 publications
8
31
0
1
Order By: Relevance
“…Consistent results in the literature demonstrate, over the short-term, that dietary nitrate can be successfully administered at levels capable of reducing CH 4 with no adverse effects on performance in sheep (Van Zijderveld et al, 2010;Li et al, 2012;El-Zaiat et al, 2014), goats (Nguyen et al, 2010), dairy cows (Van Zijderveld et al, 2011) and beef cattle (Huyen et al, 2010). However, a comprehensive review by Bruning-Fann and Kaneene (1993) reported a reduction in feed intake when nitrate was included in the diet at 10 g nitrate/kg DM (cattle) and 30 g nitrate/kg DM (sheep).…”
Section: Discussionmentioning
confidence: 59%
“…Consistent results in the literature demonstrate, over the short-term, that dietary nitrate can be successfully administered at levels capable of reducing CH 4 with no adverse effects on performance in sheep (Van Zijderveld et al, 2010;Li et al, 2012;El-Zaiat et al, 2014), goats (Nguyen et al, 2010), dairy cows (Van Zijderveld et al, 2011) and beef cattle (Huyen et al, 2010). However, a comprehensive review by Bruning-Fann and Kaneene (1993) reported a reduction in feed intake when nitrate was included in the diet at 10 g nitrate/kg DM (cattle) and 30 g nitrate/kg DM (sheep).…”
Section: Discussionmentioning
confidence: 59%
“…This, combined with the abundance of TCNSL, due to its industrial applications, make it an attractive methane mitigation agent. A recent study with lambs by El-Zaiat et al (2014) reported no additive effect of CNSL (about 49% anacardic acid and 39% cardanol) and nitrate on methane emission or propionate concentration. In that study, CNSL was supplemented at about 0.14% of dietary DM (which is comparable to the application rate of TCNSL in the current experiment).…”
Section: Resultsmentioning
confidence: 94%
“…Several studies also reported an increase of acetate molar percentage with nitrate supplementation (El-Zaiat et al, 2014; Guyader et al, 2015a; Veneman et al, 2015). A shift toward acetate, whose formation from carbohydrates results in the release of [2H], could have been caused by lower [2H] availability as shown by the lower gH 2 and dH 2 when NIT was used.…”
Section: Discussionmentioning
confidence: 93%